Correlation between Microvessel Density Based on CD31 Immunohistochemical Expression and Clinicopathology of Invasive Breast Carcinoma - Bitaria Febrawati, Eka; Alferraly, T. Ibnu; Betty, Betty (Majalah Patologi Indonesia, 2023)
Background Breast carcinoma is the most common malignancy in women worldwide. Tumor size, metastases, lymph node involvement (KGB), stage and histopathological grade are significant prognostic factors in invasive breast carcinoma. Microvessel density (MVD) assessment is used to measure angiogenesis which helps predict tumor behavior and the effect of antiangiogenic therapy. MVD is a quantitative calculation of intratumoral capillary blood vessels which reflects the results of the process of angiogenesis. The aim of this study was to analyze the relationship between MVD based on CD31 immunohistochemical expression and the clinicopathology of invasive breast carcinoma. Method Cross sectional analytic study with 42 samples diagnosed with invasive breast carcinoma at H. Adam Malik General Hospital Medan. MVD is the number of small blood vessels in terms of size and diameter (arterioles and venules) with a round lumen that is positively stained with CD31 at 10 large visual fields, categorized as low if <45 blood vessels/10 LPB and high if ≥45 blood vessels/10 LPB. The relationship between MVD and several clinicopathological parameters was analyzed using the Chi-Square, Fisher's Exact and Mann-Whitney tests. Results There was a significant relationship between tumor size (p=0.029), metastasis (p=0.014), stage (p=0.002), histopathological grade (p=0.0043), LVI (p=0.002), TILs (p=0.007). Large tumor size, metastases, high histopathological stage and grade, positive LVI and high TILs were significantly associated with MVD. However, there was no significant relationship between KGB involvement (p=0.570) and MVD. Conclusion MVD is significantly related to tumor size, metastases, stage, histopathological grade, LVI and TILs, and not significantly related to lymph node involvement. MVD plays a role in the angiogenesis of invasive breast carcinoma clinicopathology.